The Use of Transitional Elements for Stress Analysis of Structures with a Technological Surface Layer by the Method of Finite Elements - Kucharski, S. (Engineering Transactions, 1994)
Some shape functions have been presented for a transitional finite element, the use of which facilitates stress analysis of a structure with a technological surface layer. An example of application of such an element for determining the state of stress in a notched specimen with a surface layer is discussed.